Defence Mechanism Styles and Personality Types among Adolescents - George, Reena (INDIAN EDUCATIONAL REVIEW, 2013)
Defence mechanisms are behavioural strategies adopted by an individual to reduce anxiety and enhance one’s sense of well-being. They establish illusory mastery over perceived threats, when real mastery is impossible. The defence mechanism style adopted by an individual may be influenced by one’s personality. In the present study, five defence mechanisms styles viz., Aggressive, Projective, Intellectualising, Intrapunitive and Repressive, were analysed in relation to the Personality Types viz., Type-A and Type-B, among adolescents studying in the secondary and higher secondary schools of Kerala. The findings revealed that adolescents belonging to different Personality Types adopt significantly different styles of defence mechanisms. Adolescents having Type-B Personality were found to adopt ’Intellectualising Style’ and ’Repressive Style’, whereas adolescents belonging to Type-A Personality adopted ’Aggressive Style’, ’Projective Style’ and ’Intrapunitive Style’.